2012
DOI: 10.1074/jbc.m112.346361
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Pyrococcus abyssi NucS Endonuclease Activity by Replication Clamp at Functional and Structural Levels

Abstract: Background: NucS, new bipolar nuclease acting on branched DNA repair substrates, interacts with proliferating cell nuclear antigen (PCNA). Results: PCNA and NucS form a stable 1:1 complex and PCNA directs the activity of NucS toward single-stranded/doublestranded DNA junctions in branched DNA substrates. Conclusion: PCNA regulates NucS activity, preventing the nonspecific cleavage of NucS on the chromatin. Significance: This study will help understand how PCNA regulates its client enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 66 publications
(70 reference statements)
1
30
0
Order By: Relevance
“…Numerous client proteins of the PCNA interact with the replication clamp via a PIP box [24,35,45], a structure which is shown to be well conserved in the C-terminal end of the Pab0431 sequence (Figure 4B). …”
Section: Resultsmentioning
confidence: 99%
“…Numerous client proteins of the PCNA interact with the replication clamp via a PIP box [24,35,45], a structure which is shown to be well conserved in the C-terminal end of the Pab0431 sequence (Figure 4B). …”
Section: Resultsmentioning
confidence: 99%
“…This procedure avoids loss of ligand from the DNR hemes upon addition. Fluorescence anisotropy was measured following a procedure as described (21) in a Cary Eclipse fluorometer equipped with a manual polarization device, with an excitation beam centered at 590 nm and scanning the Texas red emission spectrum. Anisotropy data were fitted to a hyperbolic binding curve (Langmuir equation) to determine the binding constant (K d ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore it appears that the presence of three identical surfaces on PCNA may restrict and direct the access of target proteins. In this respect, Creze et al [46] recently described the functional and structural characterization of the complex formed between PCNA and NucS, a structure-specific DNA endonuclease. They demonstrated that only one molecule of the NucS homodimer binds to the outside surface of the PCNA homotrimer via the PIP (PCNA-interacting protein)/IDCL (interdomain connecting loop) interface, leading to the conclusion that this particular stoichiometry could be due RNA primer removal in Archaea 279 to long-range conformational changes on PCNA that in turn could regulate the recruitment of additional partners [46].…”
mentioning
confidence: 99%